Shattered Encounters: From My Father’s House (1947) to My Father’s House (2008) - Steir-Livny, Liat (Pivot: A Journal of Interdisciplinary Studies and Thought, 2017)
In the aftermath of World War II, approximately 500,000 Holocaust survivors immigrated to Israel. The complex experiences of this shattered group and their encounters with Israeli society were reduced to a series of superficial representations in Israeli feature films. In films produced both in pre-state Israel, and in the early decades of the fledgling state, Holocaust survivors were depicted as traumatized individuals saved by other Jews and transformed into active, strong, healthy civilians in the new land. By the late 1970s, however, Israeli society had changed, as did the cinematic representation of the encounter between native Israelis and the Holocaust survivors. A shift to a dystopian depiction took place, in which a traumatized group of people, neglected by veteran Israelis, were relegated to the margins of society. This article will analyze the profound change that took place between earlier and later representations. It will discuss the motivating factors and cinematic depictions through the lenses of two films which tell the same story, but from completely different perspectives: My Father’s House (Herbert Klein, 1947) and My Father’s House (Danny Rozenberg, 2008). While sharing the same title, these films were produced in different eras, and thus, shed light on different depictions of similar encounters.